2017
DOI: 10.1016/j.biopsycho.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Social processing in early adolescence: Associations between neurophysiological, self-report, and behavioral measures

Abstract: Peer relationships play a major role in adolescent development, but few methods exist for measuring social processing at the neurophysiological level. This study extends our pilot study of Island Getaway, a task for eliciting event-related potentials (ERPs) to peer feedback. We differentiated ERPs using principal components analysis (PCA) and examined associations with behavioral and self-report measures in young adolescents (N = 412). PCA revealed an early negativity in the ERP enhanced for rejection feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 62 publications
15
68
1
Order By: Relevance
“…Our findings also replicated earlier work on the LPP to social feedback (Kujawa et al, 2017); specifically, LPP amplitudes were greater following acceptance versus rejection.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings also replicated earlier work on the LPP to social feedback (Kujawa et al, 2017); specifically, LPP amplitudes were greater following acceptance versus rejection.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the P300 was larger for acceptance relative to rejection. This finding is consistent with findings from a study that used the Island Getaway task in a large sample of adolescents (N = 412; Kujawa et al, 2017), but is inconsistent with other smaller social feedback studies (Cao et al, 2015;Dekkers et al, 2015). The P300 to "on the fence" feedback was reduced relative to acceptance and comparable to the P300 to rejection.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Next, after EEG setup, participants completed a total of five tasks. The current study focuses only on data from the picture-viewing task, and the results of other tasks administered during the same experimental sessions are presented elsewhere (Kujawa, Kessel, Carroll, Arfer, & Klein, 2017;Kujawa, Proudfit, Laptook, & Klein, 2015;Meyer, Hajcak, Glenn, Kujawa, & Klein, 2017;Meyer, Hajcak, Torpey-Newman, Kujawa, & Klein, 2015). Task order was counterbalanced across all participants.…”
Section: Procedures and Taskmentioning
confidence: 99%